Correlating Surface Crystal Orientation and Gas Kinetics in Perovskite Oxide Electrodes. Issue 20 (8th April 2021) - Gao, Ran; Fernandez, Abel; Chakraborty, Tanmoy; Luo, Aileen; Pesquera, David; Das, Sujit; Velarde, Gabriel; Thoréton, Vincent; Kilner, John; Ishihara, Tatsumi; Nemšák, Slavomír; Crumlin, Ethan J.; et al.
Abstract: Solid–gas interactions at electrode surfaces determine the efficiency of solid‐oxide fuel cells and electrolyzers. Here, the correlation between surface–gas kinetics and the crystal orientation of perovskite electrodes is studied in the model system La0.8 Sr0.2 Co0.2 Fe0.8 O3 . The gas‐exchange kinetics are characterized by synthesizing epitaxial half‐cell geometries where three single‐variant surfaces are produced [i.e., La0.8 Sr0.2 Co0.2 Fe0.8 O3 /La0.9 Sr0.1 Ga0.95 Mg0.05 O3−δ /SrRuO3 /SrTiO3 (001), (110), and (111)]. Electrochemical impedance spectroscopy and electrical conductivity relaxation measurements reveal a strong surface‐orientation dependency of the gas‐exchange kinetics, wherein (111)‐oriented surfaces exhibit an activity >3‐times higher as compared to (001)‐oriented surfaces. Oxygen partial pressure ( p O 2 )‐dependent electrochemical impedance spectroscopy studies reveal that while the three surfaces have different gas‐exchange kinetics, the reaction mechanisms and rate‐limiting steps are the same (i.e., charge‐transfer to the diatomic oxygen species). First‐principles calculations suggest that the formation energy of vacancies and adsorption at the various surfaces is different and influenced by the surface polarity. Finally, synchrotron‐based, ambient‐pressure X‐ray spectroscopies reveal distinct electronic changes and surface chemistry among the different surface orientations. Taken together, thin‐film epitaxy provides an efficient approach to control and understand the electrode reactivity ultimately demonstrating that the (111)‐surface exhibits a high density of active surface sites which leads to higher activity. Abstract : The oxygen‐exchange kinetics in the perovskite oxide La0.8 Sr0.2 Co0.2 Fe0.8 O3 are found to be strongly dependent on the exposed crystallographic surface. An all‐perovksite, epitaxial half‐cell is developed and characterized. The electrochemical performance of the different surface orientations is explained with insights from synchrotron‐based ambient‐pressure spectroscopy and density functional theory.